The role of Immigration of Indonesia in facing Terrorism - Muhammad Muqtadir Drajad Lokanasaputra (Journal of Law and Border Protection, 2019)
This paper describes the role of Indonesian Immigration in facing terrorism. One of them is the role of Immigration Intelligence set out in Law number 6 of 2011 concerning Immigration. Here the role of intelligence in following up an investigation, security, and raising, ranging from granting visas, granting DPRI, to the Immigration office and at the Immigration Checkpoint (TPI). Terrorism is a crime against humanity and civilization and is a serious threat to the sovereignty of a country. The author tries to discuss the roles of Indonesian Immigration in its efforts to deal with the problem of terrorism that has plagued various countries in the world. The role of Immigration Intelligence plays an important role in dealing with this problem if viewed from the role of Immigration Intelligence, immigration should be in terms of traffic in and out of people both Indonesian and foreigners in Indonesia.